Digital Campaign 2024: Exploration of Political Party Social Media Content in General Elections - Muhammad Amril Pratama Putra; Nursaleh Hartaman (UNIVERSITAS MUHAMMADIYAH MATARAM, 2024)
This research aims to analyze social media content as political communication used by political parties in Indonesia in delivering messages to the public through social media. The method used in this research is qualitative with data taken from the social media content of political parties and analyzed using the content analysis method with the help of NVivo 12 Plus software. The research findings show the dominance of Core Argument or the use of logical arguments, facts, data, and rational reasoning in the social media content of political parties. However, other elements such as Emotional Quality and Communicative Ideology are also found in significant portions. The results of thematic analysis reveal that Core Argument dominates with 48%, followed by Emotional Quality at 35%, and Communicative Ideology at 17%. These findings confirm the efforts of political parties to build credibility and public trust by presenting factual and rational information on social media. However, they also do not ignore the importance of building emotional connections with audiences and conveying certain ideologies or narratives in their political communications.